The Effect of Anxiety, Mental Toughness, Critical Thinking on Decision Making of Badminton Umpire - Fahmi Abdul Fatah; Herman Subarjah; Helmy Firmansyah (Bisma The Journal of Counseling, 2022)
The purpose of this study is to determine  the mediating role of mental toughness influencing the direct and indirect anxiety, critical thinking on decision making of badminton umpire. The research used a descriptive method with the analysis used path analysis. The sample consisted of 37 umpires from West Java Province who were selected using an incidental sampling method from the population of PBSI West Java umpire. The research hypothesis was tested using path analysis techniques. The research findings are: 1) Anxiety has a significant negative contribution to badminton umpire decision making. 2) Thinking critically does not contribute significantly to badminton umpire decision making. 3) Anxiety through mental toughness is significant for the decision making of the umpire. 4) Critical thinking through mental toughness contributes significantly to umpire in decision making. This conclusion is an indication that the issue of mental toughness related to decision making among umpires is a very complex problem.